Evaluation of the Risk of Truck Platoon under Crosswind regarding the Lateral Displacement on Horizontal Curves - Wentao Wu; Xiaoxiang Ma (Journal of Advanced Transportation)
Driving safety on horizontal curves under crosswinds has always been a concern for researchers. However, previous studies focused on single vehicles, especially single trucks. The safety of the truck platoon under crosswinds on horizontal curves was rarely examined. To fill such a gap, this study establishes a model for evaluating the safety of truck platoons under crosswinds on curves. After obtaining aerodynamic coefficients, a cosimulation model of a three-truck platoon is established with Trucksim and Simulink. The influencing factors on the lateral displacement of the truck platoon were analyzed, and the safety of the truck platoon under crosswinds on horizontal curves was then quantified with the response surface method. The results show that the fully autonomous platoon is safer than the human-led platoon. In a three-vehicle platoon, the smaller the lateral displacement of the truck, the further back the truck, and the lateral displacement of the vehicle increases with the loading of the truck. The safety index is computed to quantify the reliability of the truck platoon. The results indicate that the safety index increases with a decrease in the mean wind velocity and mean vehicle velocity and increases with an increase in the mean radius. When crosswinds come from the inside of the curve, the safety index increases with an increase in the mean superelevation; for crosswinds from the outside of the curve, the safety index rises with the drop of superelevation. The proposed approach can quantify the safety level of truck platoons under crosswinds on horizontal curves, and the results provide guidance to support the decision-making of transportation management agencies.